The correlation between physical activity and hypertension in menopausal women - I Gusti Ayu Agung Anindya Maharani; Putu Ayu Sita Saraswati; I Gusti Ayu Artini; Anak Agung Gede Eka Septian Utama (Universitas Udayana dan Diaspora Taipei Medical University, 2024)
Background: Hypertension is one of the deadliest diseases worldwide and ranks first among the most common diseases in Mengwi, Badung. Hypertension is characterized by persistently high blood pressure, with systolic blood pressure greater than or equal to 140 mmHg and diastolic blood pressure greater than or equal to 90 mmHg. Physical activity plays a crucial role in maintaining heart health. This research aimed to determine the relationship between physical activity and hypertension in menopausal women. Methods: The research used an analytical observational method with a cross-sectional approach. This research was conducted in August–November 2023 at Desa Penarungan, Mengwi, Badung, Bali. Purposive sampling was used as the sampling method, resulting in 80 samples. Physical activity was measured using the Global Physical Activity Questionnaire (GPAQ), and blood pressure was measured using a sphygmomanometer. Data was analyzed using the Spearman rank statistical test. Results: The statistical test showed a value of p=0.000 (p<0.005), indicating a significant relationship between physical activity and hypertension in menopausal women. The obtained correlation value was r=-0.479, which was negative and signified an inverse or opposite relationship with a relatively strong correlation level. This suggested that the lower the level of physical activity, the higher the degree of hypertension. Conclusion: There was a significant relationship between physical activity and hypertension in menopausal women.